Pelatihan Penggunaan Qris Dalam Upaya Peningkatan Produktivitas Umkm - Intan Athiyatul Maula; Dian Nofitasari; Atinal Husna Adinia; Hendri A; Ria Anisatus (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
QR Code is a series of matrix codes or dimensional barcodes that contain information such as user identity, payment amount, and currency that can be read with certain tools used for payment transactions. Currently, QRIS has begun to be widely used by MSMEs as a more efficient non-cash payment system. This research aims to help MSME players conduct sales transactions using digital payment techniques that focus on QRIS payment applications so that consumers have choices in choosing a payment system and increase knowledge or education to business actors about the advantages of digital payments. This research is a library research with a qualitative approach. The data sources in this study were obtained through interviews and various references such as books, journal articles, the internet, and other sources related to training in the use of QRIS in MSME actors. The results of this study indicate that business actors have not implemented a digital payment system because their marketing targets are children and local residents, besides that the sales location is in the village. So that there is training and making QRIS barcodes with several stages such as surveys, implementation and evaluation of how effectively QRIS is used in both objects as a safe, practical, and very appropriate digital payment to facilitate payment transactions with consumers and can increase productivity for UMKM Kedai Ersya Food and Capcin Ashilla